Analisis Potensi Pemanfaatan Marketplace Media Sosial Facebook terhadap Penjualan Usaha Mikro (UMI) Kuliner di Kecamatan Jenggawah - Hasanah, Ismiatul; Zuniana, Qory (KUBIS, 2022)
Potential use of social media marketplace Facebook to increase sales of Micro Culinary Enterprises (UMI), namely snacks, food and beverages in Jenggawah District". Appointed based on the current phenomenon where culinary micro business actors besides selling directly also sell products online. on the increase in sales carried out by micro culinary business actors (UMI) in Jenggawah District. This study uses a descriptive analysis method that focuses attention on the problem as it was at the time of the study. The sampling method in this study used a purposive sampling technique. The results showed that: The strategy that can be done by business actors in increasing their sales using the Facebook or offline social media market is an aggressive strategy. Strategies that can be done include maximizing branding, adding new menus, establishing cooperation with related partners, providing special offers and so on.